Malignant features of a benign waiting list. (March 2017) - Ally, Munira; Lee, Tiffany; Ecclestone, Hazel; Teo, Luke; Kavia, Rajesh
Objective: Transurethral resection of the prostate (TURP) operations are frequently deferred. Consequently, patients awaiting TURP have multiple urology-related admissions for problems such as urinary retention. This audit aims to determine the effect of TURP deferments on the frequency and duration of urology-related admissions, as well as the financial implication in our institution over a three-month period. Patients and methods: A retrospective, electronic database review of patients who received a TURP at Northwick Park Hospital, between 1 January 2014–31 March 2014, was carried out. The following data were extracted: (a) date the patient was listed for TURP; (b) date patient underwent TURP; (c) number of deferments between a patient being listed for surgery and receiving their operation; (d) reason(s) for deferment; and (e) number, duration and indication of urology-related inpatient admissions whilst awaiting TURP. Using this data, we calculated the cost of urology-related admissions whilst awaiting surgery. Results: In total, 44 patients underwent a TURP operation. Of these, 21 patients had their TURP deferred. There were 23 urology-related admissions whilst patients awaited a TURP. Fifteen of these admissions were attributed to eight patients with deferments to surgery. They spent a total of 45 days/30 nights in hospital. The remaining eight urology-related admissions were accounted for by six patients with no deferments to surgery. They spent 12 days/3 nights in hospital. We approximate a daily cost of £250 for an NHS bed. This equates to a total cost of £11, 250 (£1406 per patient) for the eight patients who had TURPs deferred versus £3000 (£500 per patient) for those six patients without deferments. Conclusion: Patients who have their TURP operations deferred have an increased frequency and duration of urology-related admissions, associated with an additional cost of at least £900 per patient.